Experiences of early childhood learners with physical challenges within the mainstream classroom room? : the case of a primary school in Chegutu. - Pasaya, Media (Midlands State University, 2017)
Inclusion is a fairly recent practice that has been brought about by the Salamanca Statement of 1994. Various local, regional and international instruments promoting inclusion of people living with disabilities have been conducted however it is the researchers’ opinion that most of the researches carried out on inclusion have focused more on policy, practice and educators’ perspectives and the experiences of the child with physical disabilities in the mainstream have not been fully explored. This study sought to explore the experiences of the early childhood learners with physical challenges who are included in mainstream classes at a primary school in Chegutu urban. The researcher used the case study design because of its ability to gather a lot of information directly from the respondents which would not normally be obtained by other research designs. It is the learners’ voices that play an important part of the school self-assessment, therefore they need to have their views heard because their opinions paint a true picture and also give some important indications of how inclusive practices can be challenged and supported. Early Childhood Education learners from grade one to three were purposively sampled to share their experiences within the mainstream education with the researcher. Interviews and the complete observation technique were used for collecting information. From the research findings it was established that the learners interviewed enjoyed being in the mainstream as they liked their interaction with other children, they also participated in most of the school curriculum activities. Inadequate accessibility to parts of the school was a major factor the learners said they disliked, all the learners also expressed that they had suffered from rejection such as mocking and social rejection and all learners expressed that there are activities that their disabilities prevented them from taking part in. Recommendations such as teacher adaptations to teaching strategies, physically adapting structures within the school by constructing gentle slopes on high verandas, wheelchair ramps and access routes to the classroom and respective areas were made.